The government of nature - Weaver, Afaa M. (Afaa Michael), 1951- (Pittsburgh, Pa. : University of Pittsburgh Press, 2013)
This is the second volume of a trilogy (the first was The Plum Flower Dance) in which the poet analyzes his life, striving to become the ideal poet. He explores the trauma of his childhood - including sexual abuse - using a "cartography and thematic structure drawn from Chinese spiritualism." The poet is a practitioner of Daoism, and this collection deals directly with the abuse in the context of Daoist renderings of nature as metaphor for the human body.
Buddha Reveals the Apocalypse to the Cowboy -- Evening Lounge -- The Path -- The Ten Thousand -- A Dream of Emptiness -- Tsunami -- Leaves -- Walking with Snakes -- A Monk's Ode to Guan Yin -- Guan Yin's Treatise on Compassion -- Damascus -- Flying -- If You Tell -- The Ancestors Speak to the Cowboy -- Interpretation of Tongues -- The Ancestors Explain How Envy Grew -- Scapegoat -- Elegy for the Appaloosa's Mother -- Against Forgiveness -- The Government of Nature -- For James -- The Pantry -- Germany, in the Fifties -- In the Park with My Grandchildren -- Remember -- At Lake Montebello with James -- Scrapple -- When My Heart Failed -- In Raleigh's Brownstone Hotel -- On Hearing Beethoven's Moonlight -- Looking Up from the Naked Bed -- The Touched -- The Untouched -- In Good Samaritan Hospital -- Driving South from Salem -- With My Family at Dinner on Easter Sunday -- Evensong at Christ Church -- Washing the Car with My Father -- Petunias -- Cold Mountain -- Passing through Indian Territory -- Predators -- Weeping Willow -- 1963 -- Drowning -- A Nightmare -- To Those Who Would Awaken -- The One Song of He Nan Monastery.
Print version record.
JSTOR
Keywords: American poetry -- African American authors -- 21st century; Poésie américaine -- Auteurs noirs américains -- 21e siècle.; LITERARY CRITICISM -- Poetry; POETRY -- American -- General; American poetry -- African American authors; 2000-2099; Electronic books